Assessment of landscape thresholds for lesser prairie-chickens in Kansas - Stafford, Katryn Hannah (My University, 2026)
The lesser prairie-chicken (Tympanuchus pallidicinctus) is a grassland-obligate prairie grouse found in the southwestern Great Plains of the United States and currently occurs in four distinct ecoregions (Short-Grass Prairie/CRP Mosaic, Mixed-Grass Prairie, Sand Sagebrush Prairie, and Sand Shinnery Oak Prairie) across five states (Colorado, Kansas, Oklahoma, Texas, and New Mexico, USA). In recent decades, lesser prairie-chickens have suffered extensive habitat loss and degradation, reduced occupied range, and population declines. Ecological and anthropogenic factors such as changes in disturbance regimes, woody encroachment, conversion of grassland for agriculture, urban expansion, and energy development are contributing to population and habitat declines. Because lesser prairie-chickens require extensive native grasslands to meet breeding, brood-rearing, and nonbreeding needs, further loss of habitat can isolate populations and reduce population persistence. My objectives were to estimate and compare land cover variables (native grassland, CRP grassland, total grassland, cropland, trees/ha, and density of anthropogenic structures) between Focal Areas (CHAT 1) designated by Western Association of Fish and Wildlife Agencies (WAFWA) and Occupied Areas delineated by survey data in Kansas. On a smaller scale, I estimated land cover variables within 5 km of 335 lesser prairie-chicken leks in three different lek attendance groups (<10 males, >10 males, and Extinct leks) in Kansas. Lastly, within each lek attendance group, I determined the status of each lek relative to each ecological threshold and estimated the proportion of leks above and below thresholds in each ecoregion. Overall, the WAFWA Focal Areas (CHAT 1) exhibited differences in ecological threshold and landscape characteristics among the Short-Grass Prairie/CRP Mosaic, Mixed-Grass Prairie, and Sand Sagebrush Prairie ecoregions in Kansas. For example, Focal Areas in the Mixed-Grass Prairie Ecoregion contained greater proportions of native grassland and total grassland but had the least CRP grassland. In contrast, Focal Areas in the Sand Sagebrush Prairie Ecoregion had the greatest CRP grassland but least total grassland overall. This suggests that population threshold concerns varied according to ecoregional landscape conditions. Landscape characteristics within Occupied Areas were relatively consistent among ecoregions, suggesting that lesser prairie-chickens may be selecting for similar landscape characteristics across its occupied range in Kansas. On a smaller scale, the Short-Grass Prairie/CRP Mosaic Ecoregion had the greatest proportion of leks with >10 males (39.47%) and the least proportion of leks that were vacated during the survey period (26.32%). Overall, leks in this ecoregion were surrounded by more CRP grassland and fewer trees within 5 km when compared to other ecoregions. Within the Mixed-Grass Prairie and Sand Sagebrush Prairie ecoregions, >80% of surveyed leks were either below the threshold of 10 males or Extinct. Leks in the Mixed-Grass Prairie Ecoregion had the greatest density of trees, followed by the lowest proportion of CRP grassland within 5 km. Lastly, leks in the Sand Sagebrush Prairie Ecoregion contained the fewest trees within 5 km, but high densities of anthropogenic development and agricultural operations surrounded concentrations of leks. Finally, lek attendance groups (<10, >10, Extinct) were similar in the number of leks above and below identified ecological thresholds within each ecoregion. However, different land cover characteristics influencing threshold status were observed among ecoregions. A greater proportion of leks in the Short-Grass Prairie/CRP Mosaic and Mixed-Grass Prairie ecoregions exceeded the threshold of 2 trees/ha and were below the threshold for native grassland when compared to leks in the Sand Sagebrush Prairie Ecoregion. Conversely, the opposite pattern was observed in the Sand Sagebrush Prairie Ecoregion, as no leks exceeded 2 trees/ha and the least proportion of leks were below the threshold for native grassland. Despite these ecoregional differences, presence of CRP grassland was highly influential; once combined with native grassland, 78.51% of leks exceeded 60% grassland, representing a 30.75% increase. This emphasizes the importance of CRP grassland on the landscape and is consistent with previous research demonstrating that CRP grassland supports lesser prairie-chickens during intensive drought, nesting, brood-rearing, roosting, and dispersal movements. Overall, my results suggest that implementation of management practices should be ecoregion specific to yield the most effective results and improve the persistence of the lesser prairie-chicken in Kansas.
Keywords: Ecology; Ornithology